Decomposing Federal Funds Rate forecast uncertainty using real-time data - Martin Mandler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
Using real-time data I estimate out-of-sample forecast uncertainty about the Federal Funds Rate. Combining a Taylor rule with a model of economic fundamentals I disentangle economically interpretable components of forecast uncertainty: uncertainty about future economic conditions and uncertainty about future monetary policy. Uncertainty about U.S. monetary policy fell to unprecedented low levels in the 1980s and remained low while uncertainty about future output and inflation declined only temporarily. This points to an important role of increased predictability of monetary policy in explaining the decline in macroeconomic volatility in the U.S. since the mid-1980s.
Keywords: E52; C32; C53; 330; monetary policy reaction function; interest rate uncertainty; state-space model